The analysis of temporomandibular disorder based on RDC/TMD Axis I revision 2010 in dentistry students - Rikmasari, Rasmi; Kusumadewi, An-Nissa; Damayanti, Lisda; Dziab, Hasna; Kurnikasari, Erna (Padjadjaran Journal of Dentistry, 2016)
Introduction: Temporomandibular joint disorders is a pathologic conditions as a caused of musculoskeletal pain and dysfunction syndrome in stomatognathic system. This disorder was suffered in the population and affected the quality of life. This study was done to know how was the condition of temporomandibular joint disorders in the student of Faculty of Dentistry Universitas Padjadjaran population. Another objective of this study was the diagnosis classification of revised RDC-TMD Axis I could be applicated in Indonesian population, and to calibrate the diagnostic. Methods: The research sample was 65, with 43 female and 22 male. Result: The result showed that 50% of the student of Faculty of Dentistry Universitas Padjadjaran minimally suffered one diagnosis of temporomandibular joint disorders; with the most disorder was disc displacement with reduction, in left or right joint, followed by myofacial pain with limited opening. Conclusion: The conclusion of this research there was a high percentage of temporomandibular joint disorders in student population based on Revised Research Diagnosis Criteria for Temporomandibular Joint Disorders 2010, with the most disorder were disc displacement with reduction. So, it was important to socialize this sign and symptom of these disorders to community.